Penyelesaian Sengketa Wanprestasi Debitur Pada Perjanjian Kredit Tanpa Agunan - Fitriana, Dian; Aliya Sandra Dewi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Bank financial institutions as financial intermediaries function as financial intermediaries between parties who have excess funds and those who lack funds. After the bank has succeeded in collecting funds from the public in the form of savings (funding), it will channel these funds to the public in the form of credit or financing (lending). If credit is channeled to the public, it can be differentiated into 2 (two) types, namely collateral-free credit and collateral-seeded credit. Credit without collateral is basically quite profitable for some people who need fast funds without having to be burdened with having to guarantee their assets. It's just that this unsecured loan has drawbacks, namely high interest and a limited credit period, which is between 1 (one) to 3 (three) years. Many ordinary people do not know that when we have agreed to a credit agreement without collateral, based on Article 1131 and Article 1132 of the Civil Code, we have actually surrendered all of our assets as collateral and guarantee for our credit. So that based on articles 1131 and 1132 of the Civil Code, all of the debtor's assets will serve as collateral for the amount of debt that must be paid by the debtor. This is not generally known by the public or those who receive credit without collateral. So the purpose of this study is to provide education so that people are more careful in taking credit without collateral, and to find out how to resolve disputes by banks if there are customers who default due to loans without collateral.